Differential thermal voltammetry for tracking of degradation in lithium-ion batteries - Wu,B; Yufit,V; Merla,Y; Martinez-Botas,RF; Brandon,NP; Offer,GJ (Journal of Power Sources, 2015)
Monitoring of lithium-ion batteries is of critical importance in electric vehicle applications in order to manage the operational condition of the cells. Measurements on a vehicle often involve current, voltage and temperature which enable in-situ diagnostic techniques. This paper presents a novel diagnostic technique, termed differential thermal voltammetry, which is capable of monitoring the state of the battery using voltage and temperature measurements in galvanostatic operating modes. This tracks battery degradation through phase transitions, and the resulting entropic heat, occurring in the electrodes. Experiments to monitor battery degradation using the new technique are compared with a pseudo-2D cell model. Results show that the differential thermal voltammetry technique provides information comparable to that of slow rate cyclic voltammetry at shorter timescale and with load conditions easier to replicate in a vehicle.